A new l2‐gain analysis framework for discrete‐time switched systems based on predictive Lyapunov function. (30th September 2021) - Wang, Ruihua; Zong, Guangdeng; Shen, Hao; Shi, Kaibo
Abstract: The work proposes the pre‐ l 2 ‐gain analysis framework based on the newly raised nonweighted pre‐ l 2 ‐gain performance index and predictive Lyapunov function, which is devoted to nonweighted l 2 ‐gain analysis and relevant control of discrete‐time switched systems under mode‐dependent average dwell time. This also provides new ideas for other disturbance‐related studies. To begin with, the predictive Lyapunov function is established for switched nonlinear systems in the sense of better reflecting future system dynamics and future external disturbances. Hence, it is achievable to develop less conservative stability and nonweighted pre‐ l 2 ‐gain criteria for switched linear systems. Further, a new disturbance‐output expression is devised to match with the nonweighted pre‐ l 2 ‐gain, whose function is to estimate and optimize the traditional nonweighted l 2 ‐gain of the underlying system through discussions. Then, a solvable condition is formulated to seek the piecewise time‐dependent gains of switching controller in a convex structure, ensuring the global uniform exponential stability with nonweighted pre‐ l 2 ‐gain and thereby attaining much smaller non‐weighted l 2 ‐gain. Finally, the simulation comprised of a circuit system and a numerical example manifests the impressive potential of the obtained results for the purpose of preferable disturbance attenuation performances.